(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the phenomenon of an outstanding athlete in a philosophical context as the embodiment of patriotism, moral idealism, and spiritual self-improvement of an individual. Special attention is given to the role of heroic figures in sports who, as symbols of national pride, contribute to strengthening the moral foundations of society and shaping the values of youth.